Validation of Spanish Versions of the Pelvic Floor Distress Inventory and Pelvic Floor Impact Questionnaire : A Multicenter Validation Randomized Study - Omotosho, Tola B. (2009)
INTRODUCTION AND HYPOTHESIS: The purpose of this study is to validate Spanish versions of the Pelvic Floor Distress Inventory (PFDI) and Pelvic Floor Impact Questionnaire (PFIQ). METHODS: Spanish versions were developed using back translation. Validation was performed by randomizing bilingual women to complete the Spanish or English versions of the questionnaires first. Weighted kappa statistics assessed agreement for individual questions; interclass correlation coefficients (ICC) compared primary and subscale scores. Cronbach’s alpha assessed internal consistency of Spanish versions. To detect a 2.7 point difference in scores with 80% power and alpha of 0.05, 44 bilingual subjects were required. RESULTS: Individual questions showed good to excellent agreement (kappa ≥ .6) for all but 8 questions on the PFIQ. ICC’s of primary and subscale scores for both questionnaires showed excellent agreement. (All ICC ≥ 0.79). All Cronbach’s alpha’s values were excellent (≥ 0.84) for the primary scales of both questionnaires. CONCLUSIONS: Valid and reliable Spanish versions of the PFIQ and PFDI have been developed.